EFL Students’ Perception of the use “Grammarly Application” as Automated Writing Evaluation (AWE) (Conference on English Language Teaching, 2023)
The purpose of this research is to find out the perceptions of EFL students about using the Grammarly application to check grammatical errors in their assignments. It also explores about the strengths and weaknesses of Grammarly Apps. This study uses Describtif qualitatif design to study students' perspectives in using Grammarly Apps. Twenty English education students in one of University in North Sumatra were purposefully chosen as the research participants. Data from this study were collected through questionnaires and interviews. The results indicated that Grammarly has several advantages and disadvantages for students, such as a clear and easy-to-understand feedback feature, it also saves students time when assessing grammar, and other useful features. Negative perspectives from students regarding the shortcomings of Grammarly are that they cannot detected the tenses use, require a strong internet signal to use grammarly apps and cannot download feedback in the form of files and have to pay to access premium Grammar features.